IMRPOVING STUDENTS’ ACHIEVEMENT IN WRITING ANALYTICAL EXPOSITION TEXT THROUGH GUIDED WRITING TECHNIQUE - Handayani Sagala; Bachtiar Bachtiar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2012)
ABSTRACT   This study concerns on improving students’ achievement in writing analytical exposition text through guided writing technique. This research was conducted by using action research method. The subject of the study was class XI IA-1 students of SMA Negeri 17 Medan, which consisted of 36 students. The research was conducted in two cycles, which each cycle consisted of three treatments. The instruments for collecting data were quantitative data (analytical exposition writing assessment) and qualitative data (diary notes, interview sheet, observation sheet, and questionnaire sheet). Based on the students’ scores, students’ writing skill kept improving in every assessment given. The mean of the students’ score for the first competence as orientation test was 68, 12, the second competence test was 71,93, the third competence test was 79,87, and the total percentage of the improvement from the first competence test to the third competence test was 93,7%. Based on diary notes, observation sheet, questionnaire sheet, and interview report, it was found that the teaching-learning process ran well. The students were active, interested, and enthusiastic in writing. The results indicated that Guided Writing Technique improved the students’ writing achievement in analytical exposition text.   Keywords: students’ achievement, writing, analytical exposition text, guided writing technique